Intercultural teaching : a critical analysis of the African Bible College in Malawi - Stauffacher, Robert W. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MTh (Practical Theology and Missiology))--University of Stellenbosch, 2010.